The KDM4A/KDM4C/NF-κB and WDR5 epigenetic cascade regulates the activation of B cells. Issue 11 (30th April 2018) - Hung, Kuo-Hsuan; Woo, Yong H; Lin, I-Ying; Liu, Chin-Hsiu; Wang, Li-Chieh; Chen, Hsin-Yu; Chiang, Bor-Luen; Lin, Kuo-I
Abstract: T follicular helper (Tfh) cell-derived signals promote activation and proliferation of antigen-primed B cells. It remains unclear whether epigenetic regulation is involved in the B cell responses to Tfh cell-derived signals. Here, we demonstrate that Tfh cell-mimicking signals induce the expression of histone demethylases KDM4A and KDM4C, and the concomitant global down-regulation of their substrates, H3K9me3/me2, in B cells. Depletion of KDM4A and KDM4C potentiates B cell activation and proliferation in response to Tfh cell-derived signals. ChIP-seq and de novo motif analysis reveals NF-κB p65 as a binding partner of KDM4A and KDM4C. Their co-targeting to Wdr5, a MLL complex member promoting H3K4 methylation, up-regulates cell cycle inhibitors Cdkn2c and Cdkn3 . Thus, Tfh cell-derived signals trigger KDM4A/KDM4C - WDR5 - Cdkn2c/Cdkn3 cascade in vitro, an epigenetic mechanism regulating proper proliferation of activated B cells. This pathway is dysregulated in B cells from systemic lupus erythematosus patients and may represent a pathological link.